Non-Contact Facial Temperature Measurement Based on Thermal Technique - Yusof, Muhammad Hadi; Mohamed, Masnani (Evolution in Electrical and Electronic Engineering, 2022)
Non-contact facial temperature measurement is one of the major fields that have involved a many of research to improve the existing system. This project aims to develop the temperature monitoring system by using the non-contact technique, by extracting the temperature feature from webcam images by using MATLAB. To obtain a result of face temperature, the RGB camera is used to detect only the facial area and measures the temperature within a specific ROI at certain points. The technique of collecting the data includes three subsystems of webcam, data processing unit, and data transmission. Image processing is used to create, process, and display images. An image will be processed into 4 steps: crop image, indexed image, floating-point image, and histogram. From the result of the percentage error data analysis, it can see that the error percentage for all subjects is not more than 15%. The measurement for infrared thermometer value which almost the same as the simulation value.